Using open voice. About the therapeutic aspects of traditional singing. - Renata Krawczyk (Maria Curie-Skłodowska University, Lublin, Poland, 2019)
The article discusses therapeutic aspects of traditional voice (open, natural, archaic). The following topics have been discussed: the influence of music on the psychophysical state of a human mind, a role of breath and being here and now in regulating an emotional state of a mind. a healing effect of master-student relationships has been presented in the article, as well as a role of humility and community. it was emphasized that the traditional music and singing can be used for collecting important therapeutic experiences.